2014
DOI: 10.1016/j.otsr.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cubital tunnel syndrome: Comparative results of a multicenter study of 4 surgical techniques with a mean follow-up of 92months

Abstract: Level IV. Multicenter retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 22 publications
0
45
2
6
Order By: Relevance
“…Ultimately, 17 studies met the inclusion and exclusion criteria. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The included studies are summarized in reverse chronological order in ►Table 1. One study included 103 endoscopic patients in a prospective comparison study along with SD and UNT procedures.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Ultimately, 17 studies met the inclusion and exclusion criteria. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The included studies are summarized in reverse chronological order in ►Table 1. One study included 103 endoscopic patients in a prospective comparison study along with SD and UNT procedures.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…3 On the other hand, anterior transposition avoids all the physiopathologic phenomena underlying ulnar neuropathy, including dynamic compression of the nerve with elbow flexion. 1,8 It is indicated with symptomatic ulnar nerve instability or if the ulnar nerve is located in a "hostile bed" (e.g., osteophytes, scarring, ganglions). 6 Because the most common compression site is the cubital tunnel, this technique appoints open release of the arcuate ligament to reduce the technical demand and minimize the risk of iatrogenic ulnar nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…This can more easily be appreciated and dealt with during open rather than endoscopic procedure. 8 Besides the aponeurotic bands within the flexor pronator muscle, the medial intermuscular septum is another possible site of secondary compression after transposition. Endoscopic release of the septum is needed but the ulnar nerve can be damaged as it turns across the proximal end of the septum.…”
Section: Discussionmentioning
confidence: 99%
“…The epicondylectomy is not popular anymore. Several clinical comparative studies [91][92][93][94], meta-analyses [95][96][97] and prospective randomized trials [98,99] have shown that in situ CubTS decompression (Figures 3A-D) is just as effective as transpositions (Figures 4A-D) provided there is no UN subluxation on elbow flexoextension [97,99]. Advantages of in situ decompression are smaller surgical incisions, less risk of medial antebrachial cutaneous nerve damage [100], no UN devascularisation [97], shorter operating time [101], smaller costs [99] and a faster recovery [102].…”
Section: Ulnar Nerve Compression At the Elbowmentioning
confidence: 99%